Criteria, indicators and levels of formed professional functional competences of future teachers of physical culture - Samsutina N.M (Kharkov National Pedagogical University, 2012)
It is shown the structural components of the functional competence of professional teachers of physical education: motivational, cognitive and action-practical. We used the following methods of scientific knowledge, as the analysis of psychological, educational and methodological literature, synthesis, comparison, generalization, specification, classification, ordering Criteria and levels of occupational functional competence of future teachers of physical education. It is determined that the high level of professional formation of the functional competence of future teachers of physical culture is characterized by the motivation to perform professional functions of a teacher of physical culture, fundamental knowledge required to perform professional functions of a teacher of physical culture, a high level of general physical fitness, pronounced specific motor abilities and skills.